1991
DOI: 10.1159/000168306
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Transformation in Native Kidneys in Renal Allograft Recipients with Long-Standing Good Function

Abstract: Acquired renal cystic disease develops in the native kidneys of patients with renal allografts with longstanding poor function. However, there has been no long-term prospective study of the regression or development of cysts in native kidneys of renal allograft recipients with good long-term function (serum creatinine: 114 ± 24 µmol/l). We followed 61 renal allograft recipients for 63.5 ± 29.0 months (mean ± SD) using computed tomography (CT scan) every 1 or 2 years after transplantation. The cyst grade at pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…It was first described by Dunnill, Millard, and Oliver in 1977 in a study of 30 long-term hemodialysis patients where 13 of those patients demonstrated bilateral cystic disease on autopsy. 4 Transplant may decrease the severity and frequency of ACKD but does not eliminate it. By 3 years on dialysis, more than 50% of patients exhibit radiologic evidence of ACKD.…”
Section: Discussionmentioning
confidence: 99%
“…It was first described by Dunnill, Millard, and Oliver in 1977 in a study of 30 long-term hemodialysis patients where 13 of those patients demonstrated bilateral cystic disease on autopsy. 4 Transplant may decrease the severity and frequency of ACKD but does not eliminate it. By 3 years on dialysis, more than 50% of patients exhibit radiologic evidence of ACKD.…”
Section: Discussionmentioning
confidence: 99%
“…However the disappearance of ACKD after transplantation is not universal (213)(214)(215)(216)(217). There are reports of children with functioning allografts who develop ACKD, as well as case reports of renal cell carcinomas occurring in native kidneys of renal allograft recipients (218).…”
Section: Components That Require Managementmentioning
confidence: 99%
“…These prevalence rates are derived from a number of studies with varying numbers of patients and durations of dialysis and recovery from transplantation; at first glance, there is apparently no significant difference among the three therapeutic modalities. However, when dialysis and transplantation patients are compared, the severity of cystic changes is seen to differ greatly [17-19, 29], with one sequential longitudinal study [19] finding much less alteration in kidneys of transplant recipients. Hemodialysis and CAPD patients exhibit a similar pre valence of acquired cystic disease [9], Prevalence of cyst formation does not depend on age [28]; a figure of 33% has been obtained in children on hemodialysis and CAPD [35].…”
Section: Acquired Renal Cystic Disease In Patients On Dialysis or Witmentioning
confidence: 99%
“…However, the process is incomplete. Several cysts may remain in the small, contracted kidney after trans plantation, and it is not known whether there is any pathogenic difference between regressed cysts and those remaining [19].…”
Section: Natural History Of Acquired Renal Cystic Diseasementioning
confidence: 99%